ANALISIS KUALITAS KAWASAN CAGAR BUDAYA SEBAGAI RUANG TERBUKA PUBLIK (Studi Kasus Lapangan Taruna Remaja Gorontalo) - Muhamad Rainaldy Putra Makale; Allis Nurdini (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: During the era of the Dutch East Indies government, the presence of Gorontalo Taruna Remaja field has become part of the historical witness of the national movement until it is used as a means of various public activities in the present time. As a cultural heritage area, the field, formerly known as the